Cooking behavior among mothers of children aged 2-5 years old in Kendari, Southeast Sulawesi, Indonesia - Intan R. Nirmala; Judhiastuty Februhartanty; Rina Agustina; Rini Sekartini (BMC, 2024)
Abstract Background Cooking at home was associated with parental feeding practices. This study aimed to explore the interplay of components in cooking behavior of mothers with young children aged 2-5 years old in Kendari city of Southeast Sulawesi, Indonesia. Methods This qualitative study involved 33 mothers from Kendari city, which was represented by each two sub-districts in coastal and mainland areas that were randomlyselected. Six focus group discussions (FGDs) were carried out using 20-item guide questions. The guide questions were developed following the Model of Goal-Directed Behavior (MGDB) theory approach exploring the components of cooking behavior i.e., skill, intention, desire, confidence, and attitude in cooking. Data analysis was performed in the field to assist decision on data saturation, followed by data analysis at desk through multilevel coding from the verbatim transcripts using NVivo R1 software. The data was analyzed thematically using pre-determined themes according to the MGDB theory. Emerging topics on enabling factors and constraints were captured to enhance our understanding of the complexity of cooking behavior. Results The mothers' mean age was about 30 years old with a comparable representation of younger and older mothers. Most mothers were housewives and accomplished secondary school level. The mothers' intention was shown as they frequently cooked at home and allocated time for cooking. The enabling factors included their knowledge about food and nutrition, food source availability, their confidence in cooking meals and following recipes, and their motivation to keep their children healthy representing some intrinsic factors. The main constraint was the lack of skill to make snacks. The other extrinsic barriers were dependence on mobile food sellers and the availability of food kiosks that facilitated children's snack preferences. Conclusion The study obtained some insights that mothers had favorable cooking intention and desire, were supported with a confidence in some basic cooking skills. However, the existing constraints that encouraged the development of unfavorable children's snacking habit were beyond the mothers' control. A cookbook specifically for snack recipes that utilizes local ingredients may assist mother in preparing more healthier options for the children.